PELAYANAN KESEHATAN SAPI BALI DI WILAYAH LINGKAR KAMPUS UNIVERSITAS UDAYANA BUKIT JIMBARAN KECAMATAN KUTA SELATAN KABUPATEN BADUNG - Suarsana, I. N.; Suatha, I. K.; Sampurna, P.; Kardena, I. M.; Suardana, I. W.; Utama, I. H. U (Buletin Udayana Mengabdi, 2016)
One of the obstacles that are often faced in livestock raising is a matter of disease. Even sometimes farmers suffered economic losses and no longer breeding due to the death of livestock. The health service is one of the factors that determine the success of a farm. The aim of this implemented service to improve health of bali cattle by through health services which include spraying, provision of vitamins and treatment of cattle at University of Udayana Campus around area Jimbaran Hill. Results of community service activities on cattle at University of Udayana Campus around area Jimbaran Hill, showed a positive response and a high enthusiasm of livestock farmers, that shown with the large number of cattle (37 cattle ) which can be given a livestock health services. The number and type of service animal on the farm is dominated by provision of vitamins as much as 32 cattle (86.48%), spraying action of 30 cattle (81.08%), worm medication of 7 cattle (18.92%), and administration of antibiotics of 6 cattle (16.21%). Breeders appreciate the service activities of the Institute for Research and Community Services and hope a sustainable because it was felt useful.
Keywords: Health service; bali cattle; vitamin; spraying